2014
DOI: 10.1007/s10803-014-2071-4
|View full text |Cite
|
Sign up to set email alerts
|

Age Related Differences of Executive Functioning Problems in Everyday Life of Children and Adolescents in the Autism Spectrum

Abstract: Numerous studies investigated executive functioning (EF) problems in people with autism spectrum disorders (ASD) using laboratory EF tasks. As laboratory task performances often differ from real life observations, the current study focused on EF in everyday life of 118 children and adolescents with ASD (6-18 years). We investigated age-related and individual differences in EF problems as reported by parents on the Behavioral Rating Inventory Executive Functions (BRIEF: Gioia et al. in Behavior rating inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
65
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 65 publications
14
65
2
Order By: Relevance
“…Based on the discussion in non-experimental research whether an increase in planning difficulties in ASD can be found around adolescence (Van den Bergh et al 2014 versus Rosenthal 2013), we also inspected a quadratic relationship. We inserted age as a centered quadratic predictor, and found no support for a quadratic association between age and planning performance (Q AGE 2  = 2.62, p  = .11).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the discussion in non-experimental research whether an increase in planning difficulties in ASD can be found around adolescence (Van den Bergh et al 2014 versus Rosenthal 2013), we also inspected a quadratic relationship. We inserted age as a centered quadratic predictor, and found no support for a quadratic association between age and planning performance (Q AGE 2  = 2.62, p  = .11).…”
Section: Resultsmentioning
confidence: 99%
“…Hill 2004; Lopez et al 2005; Van den Bergh et al 2014). They have trouble organizing their daily life, maintaining (social) activities or coping with unregulated stretches of time (APA 2013; Ozonoff et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bora and Murray 2014; Giakoumaki 2012; Ziermans 2013), although results have been mixed concerning their added use for predicting psychotic onset on an individual level (Fusar-Poli et al 2012; Lin et al 2013; Metzler et al 2016; Ziermans et al 2014). Executive dysfunction has also been historically linked to ASD (Pennington and Ozonoff 1996) and impairments have been widely reported (for a review see Russo et al 2007), albeit within the context of large individual and age-dependent differences (Pellicano 2010; van den Bergh et al 2014). Such individual differences in ASD may also partially account for the observed symptomatic overlap with psychotic disorders, but only a limited amount of studies have addressed this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Although deficits in executive functioning are not a specific feature of ASD individuals, they have more problems associated with executive dysfunction than healthy controls [108,129,130]. Furthermore, problems of executive dysfunction are not necessarily related to the severity of ASD symptoms [131][132][133]. Even though individuals, who at a young age were diagnosed with an ASD, are no longer met diagnostic criteria for ASD with age, these individuals still have more difficulty in several components of executive functioning (e.g., set-shifting and working memory) than healthy controls [130].…”
Section: Difficulty In Diagnosing Mild Type Of Asdmentioning
confidence: 98%